Pinkalicious & Peterrific. Pinkatastic pets! [videorecording (DVD)] (Pinkalicious & Peterrific (Television program), 2019)
Join Pinkalicious and her brother Peter for five pinkatastic adventures in Pinkville. While enjoying a day at the beach, Rafael's dog Rusty digs up a pink bone. Can Pinkalicious and the gang use their imaginations to figure out which creature it belongs to? Then, watch what happens when a pink duckling follows Peter around, and watch as unexpected guests buzz over to a pinkerrific tea party.